Clinical characteristics and outcomes of non-cystic fibrosis patients with Burkholderia cepacia complex bacteremia at a medical center in Taiwan - Tien-Hao Chang; Yu-Chung Chuang; Jann-Tay Wang; Wang-Huei Sheng (Journal of Microbiology, Immunology and Infection, 2022)
Background: Burkholderia cepacia complex (BCC) represents a group of multidrug-resistant gram-negative bacteria that cause infections among immunocompromised hosts. Bacteremia occurs in patients who are chronically ill and is associated with substantial morbidity and mortality. The aim of this study was to investigate the clinical characteristics and outcomes of BCC bacteremic patients without cystic fibrosis. Methods: We conducted a retrospective study at the National Taiwan University Hospital. Adults with BCC bacteremia from January 2015 to May 2019 were enrolled. The primary outcome was 14-day mortality. Multivariable logistic regression was performed for outcome analysis. Results: One-hundred and ninety-five patients were analyzed and their mean age was 67 years. Over 95% of the BCC isolates were susceptible to trimethoprim/sulfomethoxazole (TMP/SXT). Levofloxacin resistance rates were high, with only 25.1% of isolates being susceptible. Pairwise comparisons were made between different definitive regimens including meropenem-monotherapy, ceftazidime-monotherapy, levofloxacin-monotherapy, TMP/SXT-monotherapy, tigecycline-monotherapy as well as combination versus monotherapy. No regimen was significantly associated with survival in our study. Multivariable logistic regression showed that the Pitt bacteremia score (adjust odds ratio [aOR],1.46; 95% confidence interval [CI],1.19–1.79; p < 0.001), underlying metastatic cancer (aOR, 2.73; 95% CI, 1.01–7.39; p = 0.047), inappropriate definitive treatment independently predicted greater 14-day mortality (aOR, 8.21; 95% CI, 2.49–27.08; p < 0.001). Conclusions: No single regimen is associated with improved mortality. After adjusting for other potential confounders, our data suggest selection of an appropriate antibiotic provide better clinical outcomes among patients with BCC bacteremia.